A case for object capabilities as the foundation of a distributed environmental model and simulation infrastructure. (October 2022) - Berg-Mohnicke, Michael; Nendel, Claas
Abstract: With the advent of increasingly powerful computational architectures, scientists use these possibilities to create simulations of ever-increasing size and complexity. Large-scale simulations of environmental systems require huge amounts of resources. Managing these in an operational way becomes increasingly complex and difficult to handle for individual scientists. State-of-the-art simulation infrastructures usually provide the necessary resources in a centralised setup, which often results in an all-or-nothing choice for the user. Here, we outline an alternative approach to handling this complexity, while rendering the use of high-performance hardware and large datasets still possible. It retains a number of desirable properties: (i) a decentralised structure, (ii) easy sharing of resources to promote collaboration and (iii) secure access to everything, including natural delegation of authority across levels and system boundaries. We show that the object capability paradigm will cover these issues, and present the first steps towards developing a simulation infrastructure based on these principles. Highlights: We revive object capabilities to manage privacy in co-development efforts. We propose decentralised computing to foster collaboration in model development. We outline a blueprint for an object capability-assisted infrastructure. We present Cap'n Proto as a useful protocol for object capability implementation.